Disinformasi Pemilu Digital sebagai Ancaman Transnasional: Implikasi terhadap Kedaulatan Demokrasi Indonesia - Tazkia Nazdifa Assyahida (Lembaga Pengembangan Kinerja Dosen, 2025)
Disinformation in digital elections has emerged as a serious challenge to democracy in Indonesia, particularly when its dissemination involves cross-border actors and platforms. This phenomenon not only diminishes the quality of political participation and public trust in election outcomes, but also poses a threat to the state's information sovereignty. This study aims to identify the dominant forms of disinformation during the 2019 Presidential Election and leading up to the 2024 election, while analyzing their impact on democratic stability and Indonesia’s position in the global context. The findings indicate that political disinformation is systematically spread through social media by networks of domestic buzzers and anonymous accounts suspected to be connected with transnational actors. The consequences include heightened societal polarization, the delegitimization of electoral institutions, and increasing non-military foreign interference in domestic politics. These findings underscore the urgent need for more adaptive national strategies and international cooperation in establishing fair, transparent, and sovereignty-respecting information governance frameworks in democratic states.